CODE SWITCHING ANALYSIS OF VARIOUS PROFESSIONS IN BOY WILIAM’S VIDEO ON YOUTUBE - Noralfia, Noralfia; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This research analyzes three YouTube videos by Nessie Judge entitled “Exlusive! BCL Opens Chronology of Events That Night!, Jerome Polin Happy National Examination Canceled!!! and Najwa Shihab's Choice About President 2019! Boy William Laughing!”. The analysis mainly concentrated more on the switching of codes that was done by Boy William and the people he invites to collaborate with in his videos. This study aims to determine the types of code switching used by Boy William and the people he invites to collaborate with in his videos and find out the reasons why he uses them. This research provided use of descriptive analytic method and primarily concentrates on the ideas put forth by Hoffman and Poplack. The data in the data for this research came from transcripts of Boy William's videos, other data were collected from various citations including publications such as books, journals, articles, and theses, in addition to online sources. The data analysis techniques used in this study are based on Miles, Hiberman and Saldana including data collection, data condensation, data display, and finally drawing inferences from the findings in order to arrive at a conclusion. The final results of this study show that the utterances performed by various professions in their videos use 3 types of code switching including, intra-sentential switching, inter-sentential switching, and tag switching. As well as showing the function of using code switching used by various professions in their videos.